The role of the zinc transporter SLC30A2/ZnT2 in transient neonatal zinc deficiency. Issue 10 (30th June 2017) - Golan, Yarden; Kambe, Taiho; Assaraf, Yehuda G.
Abstract : Transient neonatal zinc deficiency (TNZD) results from loss of function mutations in the SLC30A2/ZnT2 gene. Nursing mothers harboring this defective zinc transporter produce zinc-deficient milk. Consequently, their exclusively breastfed infants develop severe zinc deficiency. The present review summarizes our current knowledge on SLC30A2/ZnT2 gene mutations and highlights the molecular mechanisms underlying this zinc deficiency. We further propose novel approaches for the early diagnosis and prevention of TNZD. Abstract : Breast milk is the optimal nutrient mix for infants until the age of 6 months. However, in some cases, due to genetic alterations as well as nutrient deficiencies in nursing mothers, infants may suffer from inadequate levels of micronutrients upon exclusive breastfeeding. In this respect, transient neonatal zinc deficiency (TNZD) is caused by loss-of-function mutations in the zinc transporter SLC30A2/ZnT2 gene, resulting in poor secretion of zinc into the breast milk. Consequently, infants exclusively breastfed with zinc-deficient breast milk develop severe zinc deficiency. The main initial symptoms of zinc deficiency are dermatitis, diarrhea, alopecia, and loss of appetite. Importantly, zinc supplementation of these zinc-deficient infants effectively and rapidly resolves these TNZD symptoms. In the current review, we present the major steps towards the identification of the molecular mechanisms underlying TNZD and propose novel approaches that could be implemented in order to achieve an early diagnosis of TNZD towards the prevention of TNZD morbidity. We also discuss the importance of assessing the prevalence of TNZD in the general population, while taking into consideration its autosomal dominant inheritance that was recently established, also supported by a large number of SLC30A2/ZnT2 variants recently identified in American lactating mothers. These findings indicating that TNZD is more frequent than initially thought, along with the increasing number of TNZD cases that were recently reported worldwide, prompted us here to highlight the importance of early diagnosis of SLC30A2/ZnT2 variants in order to supplement zinc-deficient infants in real-time, thus preventing TNZD morbidity and enhancing newborn health. This early genetic diagnosis of zinc deficiency could possibly prove to be a useful platform for the identification of other micronutrient deficiencies, which could be readily resolved by proper real-time supplementation of the infant's diet.